ImmuneDEX: a strategy for the genetic improvement of immune competence in Australian Angus cattle. (2nd March 2021) - Reverter, Antonio; Hine, Brad C; Porto-Neto, Laercio; Li, Yutao; Duff, Christian J; Dominik, Sonja; Ingham, Aaron B
Abstract: In animal breeding and genetics, the ability to cope with disease, here defined as immune competence (IC ), with minimal detriment to growth and fertility is a desired objective which addresses both animal production and welfare considerations. However, defining and objectively measuring IC phenotypes using testing methods which are practical to apply on-farm has been challenging. Based on previously described protocols, we measured both cell-mediated immune response (Cell-IR ) and antibody-mediated immune response (Ab-IR ) and combined these measures to determine an animal's IC. Using a population of 2, 853 Australian Angus steers and heifers, we compared 2 alternative methods to combine both metrics into a single phenotype to be used as a tool for the genetic improvement of IC. The first method, named Z MEAN, is obtained by taking the average of the individual metrics after subjecting each to a Z -score standardization. The second, ImmuneDEX (IDEX ), is a weighted average that considers the correlation between Cell-IR and Ab-IR, as well as the difference in ranking of individuals by each metric, and uses these as weights in the averaging. Both simulation and real data were used to understand the behavior of Z MEAN and IDEX. To further ascertain the relationship between IDEX and other traits of economic importance, we evaluated a range of traits related to growth, feedlot performance, and carcass characteristics. We report estimates of heritability of 0.31 ± 0.06 for Cell-IR, 0.42 ± 0.06 for Ab-IR, 0.42 ± 0.06 for Z MEAN and 0.370 ± 0.06 for IDEX, as well as a unity genetic correlation ( r g ) between Z MEAN and IDEX. While a moderately positive r g was estimated between Cell-IR and Ab-IR ( r g = 0.33 ± 0.12), strongly positive estimates were obtained between IDEX and Cell-IR ( r g = 0.80 ± 0.05) and between IDEX and Ab-IR ( r g = 0.85 ± 0.04). We obtained a moderately negative r g between IC traits and growth including an r g = −0.38 ± 0.14 between IDEX and weaning weight, and negligible with carcass fat measurements, including an r g = −0.03 ± 0.12 between IDEX and marbling. Given that breeding with a sole focus on production might inadvertently increase susceptibility to disease and associated antibiotic use, our analyses suggest that ImmuneDEX will provide a basis to breed animals that are both highly productive and with an enhanced ability to resist disease.